An Argument for Fewer Clinical Trials - Borgerson, Kirstin (The Hastings Center report, 2016)
The volume of clinical research is increasing exponentially—far beyond our ability to process and absorb the results. Given this situation, it may be beneficial to consider reducing the flow at its source. In what follows, I will motivate and critically evaluate the following proposal: researchers should conduct fewer clinical trials. More specifically, I c onsider whether researchers should be permitted to conduct only clinical research of very high quality and, in turn, whether research ethics committees (RECs) should prohibit all other, lower-quality research, even when it might appear to meet some minimal ethical standard. Following a close analysis of the social-value requirement of ethical clinical research, I argue that this proposal is defensible. The problem identified in this paper has two parts, quantity and quality, and some clarification is needed about the latter because “quality” is a highly contested term in the medical literature. When some scholars advocate for high-quality trials, they mean large-scale, simple, explanatory randomized controlled trials. Others, including myself, have defended a different characterization of high-quality research that tends more toward pragmatic trial design and the use of methods other than RCTs. Pragmatic trials aim to provide evidence that directly supports clinical decision-making in “usual” care settings. Unlike explanatory trials, which aim to abstract away from particular settings and patients, in the hopes of creating ideal conditions for the success of an intervention, pragmatic trials deliberately pursue knowledge of high applicability, through the use of representative subjects, clinically important questions, flexible treatment protocols, patient-oriented outcome measures, and so on. I see applicability as a marker of high-quality research. The context in which research is meant to be applied should be the context in which new interventions are evaluated.